Keys to attracting attention in advertising production through archives, image banks and music libraries in times of Covid19 - Marcos Recio, Juan Carlos; Parras Parras, Alicia (Revista General de Información y Documentación, 2021)
This article analyzes the ten most viewed campaigns during confinement in Spain, specifically during the month of April. Its objective is to know how they were made from pieces obtained in image banks and in advertisers’ archives, taking into account that the global health situation influenced the production of these advertisements, but also their consumption by users. The content analysis was carried out based on four categories: visual aesthetics of the piece; music of the piece; narration (linear, storytelling, multiplatform); and, lastly, the message of the campaign is analyzed in order to find out what emotion it is trying to convey (optimism, joy, empathy). It is concluded that both the image banks and the advertising archives of the companies are assets of great importance that have allowed creatives to develop simple campaigns to empathize with the confined viewer. Other campaigns, perhaps more original from the creative point of view, have been carried out thanks to everyday digital tools such as the smartphone and applications such as Zoom, Skype or WhatsApp.